1995
DOI: 10.1515/dmdi.1995.12.3-4.189
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Evolution of Plant P450 and P450-Reductases

Abstract: Fig. 5: Conservation of functional domains in CPRs from plant, animal, yeast and B. megaterium (the accession numbers of the sequences are given in the text). Residues printed in bold are conserved in other members of the FNR family.The numbering refers to positions in the sequence. 201Brought to you by |

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
116
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(118 citation statements)
references
References 18 publications
2
116
0
Order By: Relevance
“…29 and 30 and references therein). Phylogenetic analysis placed CYP720B1͞B2 and CYP716B1͞B2 into the CYP85 clan (31) containing several known P450s of diterpenoid (taxol and gibberellin) and triterpernoid (brassinosteroid) metabolism (see Fig. 7, which is published as supporting information on the PNAS web site).…”
Section: Resultsmentioning
confidence: 99%
“…29 and 30 and references therein). Phylogenetic analysis placed CYP720B1͞B2 and CYP716B1͞B2 into the CYP85 clan (31) containing several known P450s of diterpenoid (taxol and gibberellin) and triterpernoid (brassinosteroid) metabolism (see Fig. 7, which is published as supporting information on the PNAS web site).…”
Section: Resultsmentioning
confidence: 99%
“…A phylogenetic analysis of all characterized CYP79 enzymes and the four P. trichocarpa CYP79 sequences showed that the poplar CYP79 proteins group together with other members of the CYP79D subfamily (see Supplemental Figure 2 online), which were described to be involved in the biosynthesis of cyanogenic glycosides (Andersen et al, 2000;Forslund et al, 2004). Motifs reported to be conserved in nearly all P450 enzymes, such as the ProProxxPro motif right before the N-terminal membrane anchor, the heme binding site including the conserved Cys residue, and the ProGluArgPhe motif (Durst and Nelson, 1995), were also found in the P. trichocarpa sequences (see Supplemental Figure 3 online). Moreover, the heme binding site as well as the ProGluArgPhe motif showed substitutions unique for the CYP79 family.…”
Section: L-phe Is the Precursor Of Aromatic Nitrogenous Poplar Volatilesmentioning
confidence: 99%
“…Moreover, the heme binding site as well as the ProGluArgPhe motif showed substitutions unique for the CYP79 family. In comparison to the consensus sequence ProPheGlyxGlyArgArgxCysxGly described for A-type P450s (Durst and Nelson, 1995), the heme binding motifs of both CYP79D6v3 and CYP79D7v2 (457-SerPheSerThrGlyLysArgGlyCysIleGly-467; see Supplemental Figure 3 online) contained three amino acid substitutions which have been reported for other members of the CYP79 family (Bak et al, 1998a;Andersen et al, 2000;Nielsen and Møller, 2000). The ProGluArgPhe motif (residues 434 to 440; see Supplemental Figure 3 online) was altered to ProGluArgHis with a His substitution being unique for the CYP79 family (Bak et al, 1998a).…”
Section: L-phe Is the Precursor Of Aromatic Nitrogenous Poplar Volatilesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arabidopsis genome contains 272 cytochrome P450 genes (including 26 pseudogenes; Rhee et al, 2003;Wortman et al, 2003) of which 33 have been grouped together in the CYP86 clan of non-A-type P450s, which include the subfamilies CYP86, CYP94, CYP96, and CYP704 (Durst and Nelson, 1995;Nelson et al, 2004). Members from this clan have previously been shown to be involved in the hydroxylation reactions of fatty acyl-derived substrates (Kahn et al, 2001;Wellesen et al, 2001;Werck-Reichhart et al, 2002) and therefore genes within this clan may be regarded as candidates for cuticle biosynthetic enzymes.…”
mentioning
confidence: 99%